2015
DOI: 10.1016/j.bios.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed, label-free detection of biomarkers using aptamers and Tunable Resistive Pulse Sensing (AptaTRPS)

Abstract: Citation: BILLINGE, E.R. and PLATT, M., 2015. Multiplexed, label-free detection of biomarkers using aptamers and Tunable Resistive Pulse Sensing (AptaTRPS). Biosensors and Bioelectronics, 68, Additional Information:• NOTICE: this is the author's version of a work that was accepted for publication in Biosensors and Bioelectronics.Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be re- we believe are inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 41 publications
0
59
0
Order By: Relevance
“…The immobilization of oligonucleotides onto surfaces is a key design to many technologies within DNA sequencing 1,2 , DNA-protein interactions [3][4][5] , biosensing [6][7][8][9] and targeted drug delivery [10][11][12] . The functionalization of DNA onto nanoparticle surfaces is now a common practice, and within the field of biosensors alone the number of strategies for immobilization, type of nanomaterial, and detection platform are varied enough to fill several reviews [13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of oligonucleotides onto surfaces is a key design to many technologies within DNA sequencing 1,2 , DNA-protein interactions [3][4][5] , biosensing [6][7][8][9] and targeted drug delivery [10][11][12] . The functionalization of DNA onto nanoparticle surfaces is now a common practice, and within the field of biosensors alone the number of strategies for immobilization, type of nanomaterial, and detection platform are varied enough to fill several reviews [13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate sample handling and assay speed some RPS strategies have included nanomaterials by either immobilising the target analytes onto their surface facilitating an analyte induced aggregation 35,36 , or measuring the particle translocation speed/ frequency upon the binding of the analyte 11,30,[37][38][39][40] . With the charge of the particle being a contributing factor in pore translocation speed and frequency, the use of DNA modified materials, and pores, has become increasingly popular 11,30,[41][42][43] .…”
Section: Assay 1 -Measuring Translocation Times From Resistive Pulsesmentioning
confidence: 99%
“…The use of nanoparticle based systems may allow for multiplexed assays and faster reaction times. 32,33 The addition of charged particles into a pore exhibiting rectification behaviour is however more complex. White and co-workers demonstrated that a negatively charged particle passing through a pore with a negative surface charge can create a conductive pulse prior to the resistive pulse at a negative polarity.…”
Section: Introductionmentioning
confidence: 99%
“…31 As with all RPS sensors the only consumable is the tunable pore, eliminating the need for a carrier gas, fluidics, or optics. TRPS has been validated to accurately determine the concentration, size and surface charge of dispersed inorganic particles 24,[32][33][34][35][36][37] as well as the concentration of a range of biological analytes, which have been reviewed previously. 38,39 Conical nanopores, as used within TRPS, exhibit ionic rectification properties.…”
Section: Introductionmentioning
confidence: 99%